Implementasi Algoritma K-Means untuk Pengelompokkan Lama Sembuh Pasien Covid-19 - Nadya Octavianna Lompoliuw; Hindriyanto Dwi Purnomo (KITA Institute, 2023)
COVID-19 (coronavirus disease 2019) is a disease caused by infection with the severe acute respiratory syndrome Coronavirus 2 (SARS-CoV-2). COVID-19 can cause disturbances in the respiratory system, ranging from mild symptoms such as flu, cough to lung infections. The spread of this virus is still happening, therefore the purpose of this study is so that the public can find out more information about COVID-19, one of which is the recovery time for COVID-19 patients consisting of 4 clusters, which are very long, long, fast, and very fast. judging by the length of the recovery. Grouping the recovery time of COVID-19 patients based on age, positive date and negative date using the K-Means Algorithm. The K-Means algorithm is an iterative grouping that partitions the data set into a number of K clusters that have been determined in the initial data. Of the 4 clusters that have been determined, the results obtained are cluster 1 (very long) which is the cluster that has the longest recovery time, which is 41-48 days with ages 31 and 48 years. It can also be seen based on the symptoms experienced at each different age, on average all experience symptoms of fever and cough.